Glacial Lake in the Richardson and Rae River Basins, Northwest Territories - Mercier, Alain (Géographie physique et Quaternaire, 1984)
ABSTRACTSystematic mapping of the surficial deposits in the Richardson River basin, south and west of Coppermine, District of Mackenzie, N.W.T. has yielded strong evidence for the former existence of a glacial lake. A sequence of glacial lakes occupied an extensive portion of the basins drained by the Richardson and Rae rivers. Water bodies were trapped in this large depression to the west of Coronation Gulf by easterly retreating glacier ice. Four lake phases are recognized, each controlled by progressively lower outlets at 330 m, 260 m, 235 m and 165 m a.s.l. It is proposed that the lake which finally drained in a postglacial sea be called Glacial Lake Richardson. The former presence of the glacial lake and the associated deltas and outlets are essential elements in reconstructing the déglaciation history of the area.